Evaluation of socioeconomic status as a risk factor of pterygium using the Korean National Health and Nutrition Examination Survey 2010 to 2011: A STROBE-compliant article. Issue 11 (March 2017) - Lee, Young Bok; Kim, Su Young; Park, Yong Gyu; Han, Kyung Do; Kim, Jin-Wou; Chae, Hiun Suk; Lee, Young Chun
Abstract : Abstract: Pterygium is a common conjunctival disorder. The socioeconomic risk factors of pterygium have not been systematically evaluated in Korea. The study investigated risk factors of pterygium considering socioeconomic status. Participants were 9839 adults aged 19 to 74 years, who underwent ophthalmic slit-lamp examinations as part of the Korean National Health and Nutrition Examination Survey 2010 to 2011. Pterygium was diagnosed as a growth of fibrovascular tissue over the cornea. The socioeconomic risk factors were analyzed in association with the presence of pterygium. Multiple logistic regression analysis was used to evaluate the odds ratios for differences in socioeconomic status. The presence of pterygium was associated with diabetes mellitus, hypertension, metabolic syndrome, and sun exposure time (>5 h/d). The blood level of 25-hydroxyvitamin D was higher in the pterygium group than in the control group, but both groups were deficient in 25-hydroxyvitamin D compared with the normal reference level. Pterygium was almost 3 times as frequent among persons who worked outdoors, such as skilled agricultural, forestry, and fishery workers, than among those who worked indoors (odds ratio 3.061, 95% confidence interval 1.946–4.813). Low educational status and longer working hours were also significantly associated with pterygium. This study used a nationwide population-based survey conducted by the Korean Centers for Disease Control and Prevention to reveal that pterygium is associated with low socioeconomic status. Efforts should be made to reduce the risk of pterygium by changing modifiable risk factors, especially among people with low socioeconomic status.